Incidence and biology of beet armyworm, Spodoptera exigua in chickpea in Andhra Pradesh - Shankar, M; Babu, T Ramesh; Sridevi, D; Sharma, H C (Indian Journal of Plant Protection, 2020)
The beet armyworm, Spodoptera exigua has emerged as a serious pest of chickpea in Andhra Pradesh in recent years. Therefore, we conducted systematic surveys in the chickpea growing areas in Kurnool, Prakasam, Guntur, Medak and Mahabubnagar districts of Andhra Pradesh during the 2010/12 crop growing seasons to assess the severity of this pest. The incidence of S. exigua was high in all the districts during the early stages of the crop growth i.e., on 15-30 days old crop, and there were 11.0 to 49.4 larvae/10 plants. Minimum S. exigua numbers (15.0 larvae/10 plants) were recorded in Medak, and maximum (50.6 larvae/10 plants) in Guntur district. Larval density of H. armigera (3.2 larvae/plant), another pest damaging the chickpea during the seedling stage, was greater in Medak than in Kurnool, Prakasam and Guntur districts (1.1 larvae/10 plants). Maximum damage to the chickpea crop was observed in Kurnool district. The beet armyworm, S. exigua laid eggs in masses, which were covered with scales. The egg incubation period was longest (3.5 days) in August-September. Egg viability was highest (90.5%) in November-December and lowest in June-July (74.0%). The newly emerged larvae were light green with a shining black head. The larvae passed through five instars. Pupa was obtect, light brown in color, which later turned reddish brown. Pupal period lasted for 8.6 to 11.3 days. Moths were soft bodied, and grey brown in color. The male moth longevity was shorter (8.4 days) in June-July than in July-August (10.6 days), while the female moth longevity was shorter in August- September (8.7 days) than in July-August (10.2 days). Highest fecundity (590.6 eggs/female) was recorded in July-August and lowest in June-July (458.4 eggs/female). The total life cycle was completed in 32.6 days in May-June and 27.0 days in November-December. This information will be useful to plan pest control strategies in chickpea in Andhra Pradesh, which has witnessed the most rapid expansion in area under this crop over the past 10 years.